Papel do desempenho miocárdico na disfunção sistólica associada à doença hepática gordurosa não alcoólica - Gregolin, Cristina Schmitt (2020)
Recently, our group demonstrated that isolated steatosis, steatohepatitis, and liver cirrhosis were associated with decreasing indicators of left ventricular systolic function. The factors responsible for this connection were not investigated. The aim of the study was to evaluate whether the decrease in cardiac muscle mechanical performance is a factor responsible for systolic ventricular dysfunction associated with different stages of non-alcoholic fatty liver disease (NAFLD). In addition, the study examined whether altering the content of calcium handling proteins and the cytokines tumor necrosis factor (TNF)-α and interleukin (IL)-6 could be involved in this process. The animals were divided into four groups: control (C), sucrose (A), control and thioacetamide (C+TAA), and sucrose and thioacetamide (A+TAA). Groups C and C+TAA received standard rodent chow and natural water, while groups A and A+TAA received standard rodent chow and sucrose in the water (300 g/L). Groups C+TAA and A+TAA received thioacetamide administration (100mg/kg TAA, 2x/week/ip), while animals from groups C and A saline. The experimental period was eight weeks. Myocardial function was evaluated in vitro using isolated papillary muscle technique. Proteins involved in myocardial calcium cycle were determined by Western Blot technique and the cytokines IL-6 and TNF-α by ELISA. Comparison between groups was performed by Two Way ANOVA, complemented by Tukey. At the end of the experimental period, microscopic and macroscopic evaluation of the liver indicated that group C presented a mild degree of steatosis with normal macroscopic appearance; group A developed a moderate degree of steatosis, without inflammation / fibrosis, presenting a macroscopic aspect of the liver with slightly yellow coloration; group C + TAA presented a high degree of inflammation and fibrosis, and nodular aspect, compatible with a cirrhosis condition; group A + TAA presented moderate steatosis, mild degree of inflammation, fibrosis and a slightly yellow coloration, alterations characteristic of NASH. The liver stages of isolated steatosis and inflammation/fibrosis/cirrhosis were associated with reduced contraction strength (lower developed tension, DT). The steatosis/inflammation/fibrosis group showed no difference in DT values when compared to other stages of liver disease. All groups presented a lower response to post-rest stimulus and showed no difference to the other challenges. No differences could be found between the groups in protein expression of ryanodine, L channel, phosphorylated phospholambam in serine 16, SERCA and sodium/calcium exchanger. Groups with presence of steatosis associated or not with inflammation/fibrosis, showed an increase in the relative protein expression of phosphorylated phospholambam in threonine 17. No difference was found to TNF-α cytokine between groups. However, cardiac IL-6 content was elevated in animals with liver cirrhosis. We demonstrated that the decrease in myocardial mechanical performance is the factor responsible for the decreasing of systolic ventricular function indicators associated with the stages of NAFLD, an alteration associated with the reduced ability to restore the myocardial calcium concentration gradient. We have not shown that decreasing of myocardial contractile performance was due to a suppression in calcium handling protein content in association with the presence of IL-6 and TNF-α cytokines in the heart, but seems to depend on a metabolic change in the heart in cases associated with hepatic steatosis and inflammatory when cirrhosis is present.